2017
DOI: 10.1590/s2179-975x7617
|View full text |Cite
|
Sign up to set email alerts
|

Differences in environmental heterogeneity promote the nestedness of Chironomidae metacommunity in Neotropical floodplain lakes

Abstract: Aim: Gradients of environmental heterogeneity perform a strong influence on the distribution of organisms and determine differences in composition, where more physically complex habitats harbor greater species richness than those simpler. We took as assumptions that differences in environmental requirements of taxa promote distinct distribution patterns which are carried through to community nestedness. Therefore, we hypothesized that more heterogeneous sites hold more nested, richer and abundant communities t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
0
3
1
Order By: Relevance
“…Two primary factors, environmental heterogeneity and connectivity, are considered as critical in shaping metacommunity structure [ 3 ]. While previous studies have posited that increased environmental heterogeneity leads to stronger environmental selection [ 54 , 55 ], our results do not entirely align with this observation. The decrease in pure environmental effects in these metacommunities throughout the hydroperiod did not align with a reduction in overall environmental heterogeneity.…”
Section: Discussioncontrasting
confidence: 99%
“…Two primary factors, environmental heterogeneity and connectivity, are considered as critical in shaping metacommunity structure [ 3 ]. While previous studies have posited that increased environmental heterogeneity leads to stronger environmental selection [ 54 , 55 ], our results do not entirely align with this observation. The decrease in pure environmental effects in these metacommunities throughout the hydroperiod did not align with a reduction in overall environmental heterogeneity.…”
Section: Discussioncontrasting
confidence: 99%
“…Environmental heterogeneity has long since been described as a biodiversity predictor (Yang et al 2015;Bergholz et al 2017;Pinha et al 2017). Heterogeneous sites promote species sorting, resulting in beta diversity among local communities of a metacommunity (Pinha et al 2017;García-Girón et al 2019). This was already demonstrated in the UPRF for several biological groups, ranging from microscopic algae to fish (Padial et al 2012).…”
Section: Discussionmentioning
confidence: 85%
“…Contrary to the observed taxonomic composition, there is poor functional composition differentiation among the ecoregions that are clearly heterogeneous considering multiple ecological features. Environmental heterogeneity has long since been described as a biodiversity predictor (Yang et al 2015;Bergholz et al 2017;Pinha et al 2017). Heterogeneous sites promote species sorting, resulting in beta diversity among local communities of a metacommunity (Pinha et al 2017;García-Girón et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…We used the range of PC1 scores as a measure of EH. A similar method for measuring EH was done by Pinha, Tramonte, Bilia, and Takeda (2017) using PC1 scores and their coefficient of variation. Although we found that the variance explained by PC2 is not trivial (20.69%), we opted to retain only PC1 because it represented most of the data variation (37.66%).…”
Section: Methodsmentioning
confidence: 99%